Moringa oleifera seeds-removed ripened pods as alternative for papersheet production: antimicrobial activity and their phytoconstituents profile using HPLC - Mohamed Z. M. Salem (Nature Portfolio, 2021)
Abstract In the present study, and for the waste valorization, Moringa oleifera seeds-removed ripened pods (SRRP) were used for papersheet production and for the extraction of bioactive compounds. Fibers were characterized by SEM–EDX patterns, while the phytoconstituents in ethanol extract was analyzed by HPLC. The inhibition percentage of fungal mycelial growth (IFMG) of the treated Melia azedarach wood with M. oleifera SRRP extract at the concentrations of 10,000, 20,000, and 30,000 µg/mL against the growth of Rhizoctonia solani and Fusarium culmorum was calculated and compared with fluconazole (25 µg). The produced papersheet was treated with the ethanol extract (4000, 2000, and 1000 µg/mL) and assayed for its antibacterial activity against Agrobacterium tumefaciens, Erwinia amylovora, and Pectobacterium atrosepticum by measuring the inhibition zones and minimum inhibitory concentrations (MICs). According to chemical analysis of M. oleifera SRRP, benzene:alcohol extractives, holocellulose, lignin, and ash contents were 7.56, 64.94, 25.66 and 1.53%, respectively, while for the produced unbleached pulp, the screen pulp yield and the Kappa number were 39% and 25, respectively. The produced papersheet showed tensile index, tear index, burst index, and double fold number values of 58.8 N m/g, 3.38 mN m2/g, 3.86 kPa m2/g, and 10.66, respectively. SEM examination showed that the average fiber diameter was 16.39 µm, and the mass average of for elemental composition of C and O by EDX were, 44.21%, and 55.79%, respectively. The main phytoconstituents in the extract (mg/100 g extract) by HPLC were vanillic acid (5053.49), benzoic acid (262.98), naringenin (133.02), chlorogenic acid (66.16), and myricetin (56.27). After 14 days of incubation, M. oleifera SRRP extract-wood treated showed good IFMG against R. solani (36.88%) and F. culmorum (51.66%) compared to fluconazole, where it observed 42.96% and 53.70%, respectively. Moderate to significant antibacterial activity was found, where the minimum inhibitory concentration (MIC) values were 500, 650, and 250 µg/mL against the growth of A. tumefaciens, E. amylovora, and P. atrosepticum respectively, which were lower than the positive control used (Tobramycin 10 µg/disc). In conclusion, M. oleifera SRRP showed promising properties as a raw material for pulp and paper production as well as for the extraction of bioactive compounds.